IMPLEMENTATION OF GUIDED INQUIRY BASED PEER TUTOR TO IMPROVE STUDENT LEARNING OUTCOMES ON DYNAMIC FLUID - RAHMAWATY, NIA; ARIFIN IMAM SUPARDI, ZAINUL (Inovasi Pendidikan Fisika, 2018)
Physics learning that only fixed on definition and formula causing low student learning outcomes. Therefore, this study aims to describe the results of learning activities and student learning outcomes when applying guided inquiry based peer tutor learning model on dynamic fluid. This type of research is experimental research with one-group pretest-posttest design with replication. This research was conducted in XI IPA 1 (experiment), XI IPA 3 (1st replication), and XI IPA 4 (2nd replication) in SMAN 1 Ngronggot. The research instruments are learning activities sheet, pre-test and post-test sheets and skill assessment sheets. The increased of student learning outcomes were analyzed using paired t-test and n-gain analysis. Based on the study, it shows that the learning activities is done 100% with the quality is in good category. Student learning outcomes is improved with high n-gain scores in all three classes. Therefore, guided inquiry based peer tutor can improve student learning outcomes on dynamic fluid.Keywords: guided inquiry based peer tutor, learning outcomes